Owning Ethics: Corporate Logics, Silicon Valley, and the Institutionalization of Ethics - Metcalf, Jacob; Moss, Emanuel; boyd, danah (Johns Hopkins University Press, 2019)
Ethics is arguably the hottest product in Silicon Valley's1 hype cycle today, even as headlines decrying a lack of ethics in technology companies accumulate. After years of largely fruitless outside pressure to consider the consequences of digital technology products, the very recent past has seen a spike in the assignment of corporate resources in Silicon Valley to ethics, including hiring staff for roles we identify here as "ethics owners." In corporate parlance, "owning" a portfolio or project means holding responsibility for it, often across multiple divisions or hierarchies within the organization. Typically, the "owner" of a project does not bear sole responsibility for it, but rather oversees integration of that project across the organization.